This study will shock you an examination and analysis of clickbait articles on Facebook and its effect on audience perception of source credibility - Saunar, Ciara Marie; Khan, Rachel E.; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2018)
The study focuses on the perception of source credibility, specifically the students of University of the Philippine Diliman, when it comes to clickbait headlines posted on Facebook. A structured survey was used as a primary research instrument for quantitative and qualitative measures of the study. The questionnaire was accomplished by 200 respondents from three different colleges in the university, namely the College of Mass Communication, College of Social Sciences and Philosophy and College of Engineering. The main objective of the study was to find out if the spread of clickbait articles in social media, especially on Facebook, has an effect on the audience perception of source credibility among the respondents. The results revealed that headline plays an important role on how the readers view the credibility of a certain article and its source. Although majority of the respondents were likely to read a headline which make them curious about a certain story regardless of topic, most of them think that the way the headline is written still affects how the readers view the credibility of media outlets as sources of news stories.
Vita.
Thesis (A. B. Journalism)--University of the Philippines Diliman
Includes bibliographical references.